O problema da subdivisão dialetal madeirense: estudo dialetométrico da variação lexical - Brissos, Fernando; Raïssa Gillier; João Saramago (Revista da Associação Portuguesa de Linguística, 2016)
Despite constituting one of the most idiosyncratic varieties of European Portuguese, the dialects of Madeira and Porto Santo still lack a comprehensive characterization. This paper proposes a first classification of these dialects using a dialectometrical analysis of lexicon collected at the relevant enquiry locales of the Linguistic and Ethnographic Atlas of Portugal and Galicia. Results show that: each island is not a primary dialectal entity per se; the region’s main dialectal contrast is established by central-eastern Madeira versus western Madeira and Porto Santo; the latter’s inclusion in the western Madeira group suggests a strong dialectal unity of the whole region.